Accepting Authoritarianism : State-Society Relations in China's Reform Era. - Wright, Teresa (Stanford University Press, 2010)
This comprehensive examination of the latest and most influential research on state-society relations in post-Mao China explains why three decades of capitalist economic growth have not led to increased public pressure for liberal democratic change.